Plasmids carrying blaCTX-M-1 and qnr genes in Escherichia coli isolates from an equine clinic and a horseback riding centre - Dolejska, Monika; Duskova, Eva; Rybarikova, Jana; Janoszowska, Dagmar; Roubalova, Eva; Dibdakova, Katerina; Maceckova, Gabriela; Kohoutova, Ludmila; Literak, Ivan; Smola, Jiri; Cizek, Alois (The Journal of antimicrobial chemotherapy, 2011)
OBJECTIVES: The aim of this study was to determine the occurrence of extended-spectrum β-lactamase (ESBL)-producing Escherichia coli at an equine clinic and a horseback riding centre, and to discuss the impact of antimicrobial treatment on resistance selection. METHODS: Faeces from horses, environmental smears and flies were sampled at both the clinic and riding centre. Staff at the equine clinic were also examined. The samples were cultivated on MacConkey agar with cefotaxime (2 mg/L) to isolate ESBL-producing E. coli. The presence of bla and qnr genes was tested by PCR, and transferability was determined by conjugation. Replicon typing and restriction analysis of plasmids harbouring ESBL and qnr genes were performed. RESULTS: E. coli with the blaCTX-M-1 gene were isolated from horses, staff, environmental smears and flies at the two sites. E. coli isolates from the equine clinic harboured an IncHI1 conjugative 235-285 kb plasmid containing blaCTX-M-1, catA1, strA, sul2 and tet(B) genes. Some of these were positive for qnrS1 and/or qnrB19, and were located on 40 or 45 kb IncN or IncX1 conjugative plasmids. The gene blaCTX-M-1 in isolates from the riding centre was carried by IncN (30 kb) and IncI1 (85 kb) conjugative plasmids. Horizontal gene transfer seems to be involved in disseminating E. coli with ESBL and qnr genes at the clinic and riding centre. CONCLUSIONS: The study illustrates that ESBL-producing E. coli, as well as plasmids carrying ESBL genes of clinical interest, can be easily transferred among horses, humans and flies living in close contact.
Keywords: polymorfismus délky restrikčních fragmentů; Feces; Polymerase Chain Reaction; polymerázová řetězová reakce; Animals; molekulární sekvence - údaje; mikrobiologie životního prostředí; Conjugation, Genetic; beta-Lactamases; DNA bakterií; DNA, Bacterial; Molecular Sequence Data; Diptera; beta-laktamasy; Plasmids; Polymorphism, Restriction Fragment Length; Sequence Analysis, DNA; Escherichia coli Proteins; proteiny z Escherichia coli; Environmental Microbiology; feces; Horses; zvířata; sekvenční analýza DNA; koně; plazmidy; konjugace genetická; Escherichia coli